2017
DOI: 10.1177/0144598717743994
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation on the flow field characteristics and impact capability of liquid nitrogen jet

Abstract: With the rapid progress of petroleum engineering, liquid nitrogen jet is expected to be used for perforation and jet fracturing, and then provide a new method for unconventional reservoirs efficient development. In order to research the flow field characteristics and evaluate the impact capability of liquid nitrogen jet, a computation fluid dynamic model was built by coupling the nitrogen physical property equations to simulate the flow field of liquid nitrogen jet. The results indicated that given the same si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Cai et al [21] evaluated the flow field structure of liquid nitrogen jet by establishing a two-dimensional CFD model. In order to evaluate the flow field structure of a liquid nitrogen jet, Cai Chengzheng et al established a two-dimensional CFD model [22]. They established a computational fluid dynamics model by coupling the physical characteristic equations of nitrogen and simulated the flow field of a liquid nitrogen jet.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [21] evaluated the flow field structure of liquid nitrogen jet by establishing a two-dimensional CFD model. In order to evaluate the flow field structure of a liquid nitrogen jet, Cai Chengzheng et al established a two-dimensional CFD model [22]. They established a computational fluid dynamics model by coupling the physical characteristic equations of nitrogen and simulated the flow field of a liquid nitrogen jet.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the rock breaking and cracking capabilities will be enhanced significantly if the LNJ is used in the drilling or fracturing processes. Many previous investigations indicated that LNJ has stronger impact capability and better coal breaking performance than water jet because liquid nitrogen cooling can generate additional cracking effect on rock [7][8][9][10] The LNJ involves the heat transfer and the change in fluid properties. Thus, its flow field and jet structure will become more complex than those of the water jet will.…”
Section: Introductionmentioning
confidence: 99%